Collaboration is key: Exploring the 2021 flood response for critical infrastructures in Germany. (1st June 2023) - Nick, Florence Catherine; Sänger, Nathalie; van der Heijden, Sophie; Sandholz, Simone
Abstract: Growing dependence on critical infrastructures and exposure to natural hazards contribute to society's vulnerability to breakdowns, requiring adequate preparedness and a collaborative response during disasters. This study explores collaborative processes in the disaster response of critical water and health sectors following the 2021 floods in Western Germany. It identified key enablers and constraints for successful responses and their interactions. Organizational factors including collaboration, coordination, communication, information management and time management were key, and interacted with physical, human and social factors as well as with the overarching legal frameworks and policies within the disaster context. Lacking many enabling factors, the German flood response was insufficient, showing that critical infrastructures, their interdependencies and collaborative processes need a stronger consideration in preparedness planning. Highlights: A qualitative analysis of collaborative processes in disaster response for critical infrastructures was conducted. The German 2021 flood response lacked many enabling factors and was not need-based. Lacking account for interactions of contextual, legal, physical, human, social and organizational factors worsened impacts. Organizational factors including collaboration and coordination within and across institutions were central. Critical infrastructures and collaborative processes need stronger consideration in preparedness planning.